Relationships between respiratory symptoms, airway inflammation, sick building syndrome and allergies with indoor office environment among workers in a Malaysian University - Lim, Fang Lee (2016)
Office workers are important workforce in this modern society. However, there are only few office studies on respiratory symptoms and sick building syndrome (SBS) including clinical measurements for atopy and airway inflammation. Objective: The objective is to study the associations between indoor office environment, allergies, respiratory symptoms and SBS among office workers. Methodology: A cross sectional study was conducted among 695 office workers from 40 offices in a public university in Klang Valley. Health data were collected using a questionnaire (n=695), skin prick test (SPT) (n=463) and airway inflammation measurement [fractional of exhaled nitric oxide (FeNO) as biomarker] (n=460). Settled dust from the offices was vacuumed and analyzed for endotoxin, (1,3)-β-glucan and house dust mite (HDM) allergens namely Dermatophagoides pteronyssinus (Der p 1) and Dermatophagoides farinae (Der f 1). Indoor office temperature, relative air humidity (RH), carbon monoxide (CO) and carbon dioxide (CO2) were measured using direct reading instruments. Associations were studied using two-level linear mixed model, twolevel multiple logistic regression, stratified analysis and adjustment for personal and home environment factors using Statistical Package for the Social Sciences (SPSS) and STATA statistical package. Result: The prevalence of D. pteronyssinus, D. farinae and cat allergy among office workers were 50.3%, 49.0% and 25.5% respectively. A total of 9.6% had doctor-diagnosed asthma and 53.0% had current rhinitis. For SBS symptoms, 11.9% had weekly dermal symptoms, 16.0% had weekly mucosal symptoms and 23.0% had weekly general symptoms. One-fourth (25.5%) of the office workers had elevated FeNO levels (>25 ppb). Respiratory symptoms were associated with atopy (allergy to HDM or cat) (p<0.05) and elevated FeNO levels (p<0.05). Male gender (p<0.001), currently smoking (p=0.037), height (p<0.001) and atopy (p<0.001) were associated with FeNO levels. In particular, individuals with combination of atopy and elevated FeNO levels were associated with respiratory symptoms (p<0.050) and SBS symptoms [dermal (p=0.002), mucosal (p<0.001) and general symptoms (p=0.05)]. After adjusting for personal and home environment factors using twolevel multiple logistic regressions, endotoxin level in office dust (p<0.05) and RH (p=0.010) were associated with respiratory symptoms whereas (1,3)-β-glucan level in office dust (p=0.044), room temperature (p=0.016) and CO2 (p=0.036) were inversely associated with respiratory symptoms. The amount of sieved dust in the offices was associated with FeNO among atopic subjects (p=0.009). Der f 1 level in dust was associated with SBS (p<0.05) symptoms, especially among those with allergy to D. farinae (p<0.010). Office-related symptoms were associated with Der f 1 levels in office dust (p=0.02), low relative air humidity (p=0.04) and high office temperature (p=0.05). Conclusion: HDM and cat allergies can be risk factors for respiratory symptoms and elevated FeNO levels. A combination of allergy to cat or HDM and high FeNO can be a risk factor for respiratory and SBS symptoms. Der f 1 allergen in dust can be a risk factor for SBS in the office environment, particularly among those sensitized to Der f 1 allergen. Endotoxin levels in settled dust and low room temperature could be the risk factors for rhinitis among workers who worked in mechanical ventilated airconditioning offices in a tropical country.